Effects of a dual-task training on dynamic and static balance control of pre-frail elderly: a pilot study - Viviane Ribeiro Targino; Aline do Nascimento Falcão Freire; Ana Carolina Patrício de Albuquerque Sousa; Nícia Farias Braga Maciel; Ricardo Oliveira Guerra
INTRODUCTION: This quasi-experimental study is justified by the need to determine the effects of an intervention strategy aimed at improving the static and dynamic balance in pre-frail elderly women. We hypothesized that dual-task training on a treadmill, compared to simple training on a treadmill,may promote statistical difference in postural control of this group. OBJECTIVES: This study aimed to verify the measures of postural control in a group of pre-frail elderly after a physical therapy intervention program based on dual-task treadmill training. MATERIALS AND METHODS: We selected six female pre-frail elderly subjects living in the community. The research was conducted twice a week for 45 minutes, for four weeks. The simple task training consisted only in the use of a treadmill and the dual-task training consisted on the use of a treadmill associated with visual stimuli. Only the intervention group was submitted to the dual-task training. RESULTS: Groups showed improvements in the variables of balance in different tasks, especially on static balance. Both groups showed the most notable changes in the variables related to gait. The BBS scores and the baropodometric variables showed that the experimental group could keep all values similar or better even one month after completion of training, unlike the control group. CONCLUSION: The dual-task performance had no additional value in relation to the improvement of balance in general, but we observed that the effectiveness of visual stimulation seems to occur in the maintenance of short-term balance variables.